IDENTIFICATION OF DROUGHT TOLERANT MUTANT LINES BASED ON GENETIC VARIABILITY AND DIVERSITY STUDIES IN RICE (Oryza sativa L.) - APARNA ERAGAM*, A. SRIVIDHYA, P.LATHA, ESWARAYYA RAMI REDDY; LAKSHMINARAYANA R VEMIREDDY (The Journal of Research ANGRAU, 2021)
The study aimed to identify suitable donors for yield and drought-tolerance and its utilization in drought breeding program. A total of 10 gamma mutant rice lines and four genotypes were studied for 12 morpho-physiological parameters under moisture stress condition during rabi, 2018-2019. High genotypic coefficient of variation and phenotypic coefficient of variation values were recorded for the traits spikelets per panicle, 1000 seed weight, relative membrane injury and filled grain number per panicle under control conditions. While, under moisture stress condition filled grains per panicle, grain yield per panicle, spikelet fertility and 1000 seed weight exhibited higher GCV and PCV values. High heritability coupled with high genetic advance was observed for number of filled grains per panicle and number of spikelets per panicle under both controlled and moisture stress condition representing additive gene action whose selection might be effective in future breeding programmes. Correlation studies revealed a positive and significant association of traits plant height, panicle length, number of filled grains per panicle, spikelets per panicle, SPAD chlorophyll meter reading and specific leaf area with grain yield per plant in both control and moisture stress conditions. Divergence studies categorized the population into four clusters under control condition and three clusters under reproductive stage moisture stress conditions. Based on inter-cluster distance inclusion of genotypes under cluster II and IV in future hybridization programmes may result in the development of drought tolerant high yielding varieties.